To solve this system of equations, we can set the two equations equal to each other since they both equal to y:
3x + 3 = (1/2)x + 6
Now let's simplify the equation:
2(3x + 3) = 2((1/2)x + 6)
6x + 6 = x + 12
Next, we can subtract x from both sides:
6x - x + 6 = x - x + 12
5x + 6 = 12
Now, let's subtract 6 from both sides:
5x + 6 - 6 = 12 - 6
5x = 6
Finally, to isolate x, divide both sides by 5:
(5x)/5 = 6/5
x = 6/5
To find the corresponding y-value, substitute x = 6/5 into either of the original equations. Let's use the first equation:
y = 3(6/5) + 3
y = 18/5 + 15/5
y = (18 + 15)/5
y = 33/5
Thus, the solution to the system of equations is x = 6/5 and y = 33/5.
y = 3x + 3
y = 1/2x + 6
1 answer